Frauds in banks - Adewunmi, Wole.; Nigerian Institute of Bankers ([Lagos? Nigeria] : Landmark Publications ; [Lagos, Nigeria] : Nigerian Institute of Bankers, Lagos Branch, 1986)
The collection of papers here have been contributed by experts whose disciplines and work experiences touch intimately on the subject of frauds in banks.
Proceedings of a seminar held in Lagos, Nigeria, on Nov. 29, 1985 and organized by the Nigerian Institute of Bankers, Lagos Branch.
Includes bibliographies.
osc 19/7/17
Loans
Keywords: Banks and banking; Fraud; Bank fraud